Detection of Leishmania amazonensis and Leishmania braziliensis in Culicoides (Diptera, Ceratopogonidae) in an endemic area of cutaneous leishmaniasis in the Brazilian Amazonia. Issue 2 (17th November 2016) - Rebêlo, José Manuel Macário; Rodrigues, Bruno Leite; Bandeira, Maria da Conceição Abreu; Moraes, Jorge Luiz Pinto; Fonteles, Raquel Silva; Pereira, Silma Regina Ferreira
ABSTRACT: Biting midges in the genus Culicoides act as vectors of arboviruses throughout the world and as vectors of filariasis in Latin America, the Caribbean, and parts of Africa. Although Culicoides spp. are currently not considered to be vectors of Leishmania protozoa, the high abundance of biting midges in areas with active cutaneous leishmaniasis transmission points to the possibility of Culicoides infection by these pathogens. We used PCR to test captured Culicoides species for natural infection with Leishmania spp. We tested 450 Culicoides females, divided into 30 pools of 15 individuals each, as follows: nine pools of C. foxi (135 specimens), seven pools of C. filariferus (105), seven pools of C. insignis (105), five pools of C. ignacioi (75), and two pools of C. flavivenula (30). PCR confirmed the presence of Leishmania braziliensis DNA in C. ignacioi (0.14%), C. insignis (0.14%), and C. foxi (0.11); and Le. amazonensis DNA in C. filariferus (0.14%) and C. flavivenula (0.50%). We conclude that these Culicoide s species can be naturally infected, but vector competence and transmission capability must be confirmed in future studies. Our results warrant further investigation into the role of these biting midge species in the leishmaniasis epidemiological cycle.